Effects of sliding techniques on lower limb biomechanics and muscle synergy during curling delivery: a focus on joint kinetics and muscle coordination - Hua, Lijun; Zhu, Yulong; Bi, Gengchao; Zhu, Ming; Diao, Yuzi (Frontiers in Human Neuroscience, 2025)
BackgroundDifferent curling delivery techniques, such as full-foot contact (FFC), outward-toed full-foot contact (OTFFC), and toe contact (TC), impose distinct biomechanical demands and neuromuscular control challenges on the sliding leg. However, current research on the specific differences among these techniques in terms of multi-joint coordination and muscle synergy is limited. This study investigates the effects of these three propulsion techniques on the lower limb joint mechanics and muscle synergy patterns of the left sliding leg during curling delivery in curling athletes.MethodsKinematic and electromyographic (EMG) data from eight key sliding leg muscles (rectus femoris, vastus medialis, vastus lateralis, semimembranosus, biceps femoris, gastrocnemius, lateral gastrocnemius, tibialis anterior) were recorded from 16 male professional curlers using 3D motion capture and wireless EMG during FFC, OTFFC, and TC techniques. Muscle synergies were extracted via non-negative matrix factorization (NMF), and joint mechanics via inverse dynamics. Differences were assessed using repeated measures ANOVA.ResultsThe TC significantly altered hip and knee joint mechanics, notably increasing peak hip abduction, knee flexion, and associated torques (all p < 0.01), while also showing greater subtalar joint abduction than OTFFC (p = 0.001). Conversely, OTFFC elicited greater knee adduction angles and ankle dorsiflexion torques (p < 0.01); FFC compromised subtalar joint stability (p < 0.01). Hip and knee adduction torques were generally highest in OTFFC and lowest in TC (p < 0.001). TC demonstrated substantially higher knee flexion/extension torques (32–41%, p ≤ 0.002). Three distinct muscle synergy patterns were identified: Synergy 1 (hip-knee dominant) showed increased rectus femoris contribution in TC, while Synergy 2 (ankle-foot dominant) exhibited earlier gastrocnemius activation in OTFFC (p < 0.05 for synergy findings).ConclusionIn conclusion, the TC predominantly relies on the coordinated activation of muscle groups responsible for hip abduction, knee flexion/extension, and external rotation. Conversely, the OTFFC emphasizes the coordinated effort of muscle groups surrounding the ankle and subtalar joints. In terms of injury prevention, the concentrated use of the hip and knee joints in the TC technique suggests that targeted strengthening and stability training for these areas should be implemented to prevent potential overuse injuries.